Deduction without Dogmas:The Case of Moral Analogical Argumentation - Lilian Bermejo-Luque (Informal Logic, 2014)
a recent paper, Fábio Perin Shecaira (2013) proposes a defence of Waller’s deductivist schema for moral analogical argumentation. This defence has several flaws, the most important of them being that many good analogical arguments would be deemed bad or deficient. Additionally, Shecaira misrepresents my alternative account as something in between deductivism and non-deductivism. This paper is both an attempt at solving this misunderstanding and an analysis and criticism of Waller and Shecaira’s forms of deductivism.